Recent advances of responsive scaffolds in bone tissue engineering - Zhu, Tongyu; Zhou, Hongbo; Chen, Xiaojing; Zhu, Yuanjing (Frontiers in Bioengineering and Biotechnology, 2023)
The investigation of bone defect repair has been a significant focus in clinical research. The gradual progress and utilization of different scaffolds for bone repair have been facilitated by advancements in material science and tissue engineering. In recent times, the attainment of precise regulation and targeted drug release has emerged as a crucial concern in bone tissue engineering. As a result, we present a comprehensive review of recent developments in responsive scaffolds pertaining to the field of bone defect repair. The objective of this review is to provide a comprehensive summary and forecast of prospects, thereby contributing novel insights to the field of bone defect repair.